Antioxidant activity and combination characteristics of filtrates and sargassum polycystum seaweed salt residue: DOI: 10.48129/kjs.11807 - Nurjanah; Abdullah, Asadatun; Rahmadhani, Amalia; Seulalae, Anggrei Viona (Kuwait Journal of Science, 2022)
Sargassum polycystum is a low-sodium salt raw material, which has met the dietary salt criteria i.e. low Na:K ratio and NaCl content < 60%. This study aims to produce seaweed salt with high yield, dietary fiber content and antioxidant activity according to the quality standard of dietary salt through a combination of the filtrate and salt extraction residue. The results showed that the produced Sargassum polycystum brown seaweed salt had a Na:K ratio of 0.38, NaCl content of 49.05% and heavy metal residue below the SNI maximum standard for dietary salt. The levels of dietary fiber produced in salt samples 1:1, 1:2 and 2:1 were 34.41%, 40.16% and 23.83%, respectively and the iodine content (KIO3) of the control salt was 125.95 mg/kg. The antioxidant activity of seaweed salt (DPPH) on K salt, residue, S1, S2 and S3 was 26.41 ppm, 59.06 ppm, 12.29 ppm, 67.30 ppm and 87.50 ppm. Meanwhile, the antioxidant capacity of seaweed salt (CUPRAC) on K salt, residue, S1, S2 and S3 were 12.36, 19, 7.86, 8.52 and 12.27 μmol ascorbic acid/g extract, respectively. Therefore, it was concluded that increasing the yield and dietary fiber content in the seaweed salt production process is achievable by adding residues.